2023
DOI: 10.3390/children10030423
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Aid Successful Transition of Adolescents with Congenital Heart Disease: A Systematic Review

Abstract: The majority of patients born with congenital heart disease (CHD) need lifelong surveillance with serial clinical attendance and examinations. However, loss of follow-up (namely no documented follow-up for 3 years or more) is a recognised common problem since it is often related to remarkable worsening in the health of CHD patients with increased morbidity and mortality. Transitioning from paediatric to adult care has proven to be the most vulnerable point in the care of these subjects. As such, a systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 83 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…It is essential to delineate inequities in the transition of pediatric to adult CHD care, as this is the highest risk period for falling out of care, and lapses in care are predictors for increased morbidity and poor long-term CHD outcomes, particularly for minority populations. SDOH, such as poverty, lack of private insurance, difficulties in housing, low level of parental education, being an immigrant, being a minoritized population, shortage of food supply, and transportation barriers, are linked to several adverse clinical outcomes, including missed appointments and loss to follow-up [110,111]. Fewer than 30% of adolescents with CHD successfully transition to adult care; this percentage is even lower for minority and lower-socioeconomic-status populations [112].…”
Section: Navigation Of a Complex Medical Systemmentioning
confidence: 99%
“…It is essential to delineate inequities in the transition of pediatric to adult CHD care, as this is the highest risk period for falling out of care, and lapses in care are predictors for increased morbidity and poor long-term CHD outcomes, particularly for minority populations. SDOH, such as poverty, lack of private insurance, difficulties in housing, low level of parental education, being an immigrant, being a minoritized population, shortage of food supply, and transportation barriers, are linked to several adverse clinical outcomes, including missed appointments and loss to follow-up [110,111]. Fewer than 30% of adolescents with CHD successfully transition to adult care; this percentage is even lower for minority and lower-socioeconomic-status populations [112].…”
Section: Navigation Of a Complex Medical Systemmentioning
confidence: 99%
“…They should be encouraged to seek ACHD care even if it takes long travel so that they can consult the specialists occasionally and stay updated on their condition. Thus, even if ideal conditions for transition and continuity of care are unavailable in the region, the child and parent must be encouraged to receive a comprehensive group through telehealth, collaboration with local healthcare physicians, support networks, regular monitoring, advocacy, and self-management [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…A recent systematic review identified structured transition programs led by nurses and formal handovers to ACHD care as strategies to decrease treatment discontinuation in CHD patients. 51 The transition programs evaluated for loss to follow-up in this study employed structured transition programs, which included guidelines from Got Transition©, EMR-based transition planning tools, and shared patient information among healthcare providers. These programs were primarily nurse-led or included nurses as part of the transition team.…”
Section: Effects Of Transition Interventionsmentioning
confidence: 99%